Crystal structure of ethyl 4-[4-(dimethylamino)phenyl]-2,7,7-trimethyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate - Scott A. Steiger; Chun Li; Nicholas R. Natale (Acta Crystallographica Section E: Crystallographic Communications, 2018)
In the title racemic compound, ethyl 4-(4-dimethylaminophenyl)-2,7,7-trimethyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate, the common structural features in this type of compound, such as the flat-boat conformation of the 1,4-dihydropyridine (1,4-DHP) ring, the envelope conformation of the fused cyclohexanone, and the substituted phenyl ring at the pseudo-axial position and orthogonal to the 1,4-DHP ring, are present. In the crystal, molecules are linked via N—H...O and C—H...O hydrogen bonds, forming layers parallel to the (10\overline1) plane.